Inkar Al-Sunnah: Telaah Historis dan Sosiologis - Zikri, Abdalul; Amin, Muhammadiyah; Yahya, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The historical facts of the long journey of the Inkarus Sunnah group, ultimately must be responded to with two approaches, namely using sociological analysis and historical analysis. Sociological analysis is intended to trace the social impact of the emergence of the Inkarus Sunnah group on the integrity of the Muslim community. While historical analysis is carried out to explore information about the journey and influence of the Inkarus Sunnah group on the development of Islam from time to time. Based on this study, it can be concluded that Inkar Sunnah is a school of thought that rejects the hadith or Sunnah narrated by the Companions, either in their entirety without considering the degree of its Sunnah, and or rejects certain hadiths on the grounds that the hadith narration is not from their group or contradicts the doctrine of the school. Its emergence is due to several things, namely to better maintain the sanctity of the teachings of the Qur'an, because of differences in school of thought, because of the hypocrites, heretics, Zindiqs who pretend to convert to Islam, but actually want to destroy Islam from within as the orientalists did, and because of a lack of studying and understanding Islamic law. Denying the Sunnah is part of the slander against Islam besides the story of apostasy during the time of the companions and false prophets. In addition to continuing to study the sources of Islamic law teachings and history, Muslims must also continue to pray so that they are always on the right path, straight according to the guidance of the Qur'an and Al Sunnah.